Tbx20 Is Required in Mid-Gestation Cardiomyocytes and Plays a Central Role in Atrial Development - Boogerd, Cornelis J; Zhu, Xiaoming; Aneas, Ivy; Sakabe, Noboru J; Zhang, Lunfeng; Sobreira, Debora R; Montefiori, Lindsey E; Bogomolovas, Julius; Joslin, Amelia C; Zhou, Bin; Chen, Ju; Nobrega, Marcelo; et al. (Circulation research, 2018)
Mutations in the transcription factor TBX20 are associated with congenital heart disease. Germline ablation of Tbx20 results in abnormal heart development and embryonic lethality by E9.5. As Tbx20 is expressed in multiple cell lineages required for myocardial development, including pharyngeal endoderm, cardiogenic mesoderm, endocardium, and myocardium, the cell type specific requirement for Tbx20 in early myocardial development remains to be explored. Here, we investigated roles of in mid-gestation cardiomyocytes for heart development. Ablation of from developing cardiomyocytes using a doxycycline inducible cTnTCre transgene led to embryonic lethality. The circumference of developing ventricular and atrial chambers, and in particular that of prospective left atrium was significantly reduced in Cell cycle analysis demonstrated reduced proliferation of mutant cardiomyocytes, and their arrest at the G1-S phase transition. Genome-wide transcriptome analysis of mutant cardiomyocytes revealed differential expression of multiple genes critical for cell cycle regulation. Moreover, atrial and ventricular gene programs appeared to be aberrantly regulated. Putative direct TBX20 targets were identified using TBX20 ChIP-Seq from embryonic heart and included key cell cycle genes, and atrial and ventricular specific genes. Notably, TBX20 bound a conserved enhancer for a gene key to atrial development and identity, This enhancer interacted with the promoter in human cardiomyocytes and conferred atrial specific gene expression in a transgenic mouse in a TBX20 dependent manner. Myocardial TBX20 directly regulates a subset of genes required for fetal cardiomyocyte proliferation, including those required for the G1-S transition. TBX20 also directly downregulates progenitor-specific genes and, in addition to regulating genes that specify chamber versus non-chamber myocardium, directly activates genes required for establishment or maintenance of atrial and ventricular identity. TBX20 plays a previously unappreciated key role in atrial development through direct regulation of an evolutionarily conserved enhancer.